Tiga Gaya Tari Rantak Kudo Berpotensi Sebagai Sajian Pariwisata Di Kawasan Mandeh Dan Sekitarnya - Nerosti - Adnan (Journal of Urban Society's Arts, 2017)
This article is part of the research (2017) to analyze the style of Pesisir Selatan dance in textual and contextual. The study focuses on the style of dance Rantak Kudo from Nagari Painan Timur, Laban, and Bayang. Textual analysis includes (a) Attitude of the body; (b) Transition type of motion; (c) the dimensions of motion; (d) Active moving parts of the body; And (e) Action and effort. Contextual analysis includes the geographical areas of dance, customs, and community life structures. Descriptive evaluative method by comparing the three areas of dance development, namely Rantak Kudo dance of Talaok (Bayang), Rantak Kudo dance of Painan Timur, and Rantak Kudo dance of Laban. The discovery found that Rantak Kudo dance of Talaok  there is a tendency to make a humble movement to the earth, jerking feet rigidly to the ground closely related to the livelihood of the dominant community farming both fields and fields. Rantak Kudo dance of Painan Timur is more varied with patterned motion arrangement leads to artistic, expressing patterns of life and ways of thinking of a developing society. Rantak Kudo dance of Laban, with its close influence of the dance development area of the coast as well as the friendly and intimate style and attitudes of the people, is highly visible in the flexible or non-rigid motion style.